Model Gaya Kepemimpinan dalam Kelompok Musik Kiai Kanjeng - Muhammad Tahdianoor (JURNAL TATA KELOLA SENI, 2016)
Banyak faktor yang membuat Kiai Kanjeng memiliki banyak prestasi. Salah satu faktor pentingnya adalah gaya kepemimpinan Emha Ainun Nadjib (Cak Nun) dalam memimpin Kiai Kanjeng. Karena itu peneliti tertarik untuk mengidentifikasi karakteristik gaya kepemimpinan dan merumuskan model gaya kepemimpinan Cak Nun dalam memimpin Kiai Kanjeng. Metode penelitian yang digunakan peneliti adalah kualitatif. Hasil analisis data berdasarkan teori gaya kepemimpinan dengan pendekatan studi kasus. Pengambilan data dilakukan dengan cara observasi, dokumentasi dan mewancarai beberapa narasumber yang dianggap penting dalam penelitian ini. Berdasarkan analisa data dalam penelitian ini, karakteristik gaya kepemimpinan yang identik dengan Cak Nun secara keseluruhan cenderung memenuhi katagori gaya kepemimpinan transformasional. Gaya kepemimpinan Cak Nun yang berbeda-beda berimplikasi pada kesolidan anggota, kreatif, eksis dan mempunyai penggemar yang militan sehingga Kiai Kanjeng mampu bertahan sampai sekarang. Model gaya kepemimpinan Kiai Kanjeng yang dipimpin oleh Cak Nun yaitu, otokrasi, demokrasi, kendali bebas (laissez faire) dan partisipatif, tergantung pada kegiatan Kiai Kanjeng. Kiai Kanjeng from a standing start (1993) to the present (2016) already has been many achievements. It is the result of the leadership style by Emha Ainun Nadjib (Cak Nun) led Kiai Kanjeng. Thus the researchers are interested in identifying the characteristics of leadership style and formulate a model of leadership style in leading Cak Nun Kiai Kanjeng. Bernard M. Bass suggests that transformational leadership is the leader to encourage, motivate and innovate the members to do something beyond their own ability to improve the life of the group. The method used is a qualitative researcher. The results of data analysis are based on the theory of leadership style with a case study approach. Further data collection is done by observation, documentation and interviewed several sources that are considered in this study. Based on data analysis in this study, the characteristics of leadership style that is synonymous with Cak Nun meet category leadership style autocracy, democracy, free rein (laissez faire), participative and transformational in accordance with the activity. Cak Nun's leadership style is different implications for the solidity member, creative, exist and has fans that are militants so Kiai Kanjeng is able to survive until now. Cak Nun implements smoking-control leadership style transformational in schedulingduration exercise, discipline personnel and development staff resources (managerial). Cak Nun applies autocrary-transformational leadership style in addressing the invitation and when determining the strat-stoping song and song capabilities in the development ao lead- singger and composition/arrangement. Cak Nun apply transformational leadership style, autocrary and democratic in prepariation for staging. Cak Nun implements free rein, democratic, transformational leadership style when staging evaluation. Overall, there is a leadership style that is the same in each process, the transformational leadership style.